Factors Affecting the Intention to Receive Future COVID-19 Booster Vaccines in East Coast States in Malaysia - Mohd Nawi, Che Nur Asmani Amira Che; Mohd Nawi, Che Nur Asmani Amirah Che; Hussein, Zuhal (Information Management and Business Review, 2024)
This conceptual paper is presented to study the factors affecting the intention to receive future COVID-19 booster vaccines in three East Coast states in Malaysia, which has become a concern to the government and health system in the country. It begins by reviewing the literature on associated factors and intentions against the booster vaccination. The Theory of Planned Behavior is used as the basis of the study. This study is driven by the low vaccination rates in Kelantan, Terengganu, and Pahang. Past studies have discussed the acceptance of COVID-19 vaccination in the country, but very few focus on these states. Due to the limited findings on the issues, this study, therefore, attempts to explore the factors influencing vaccination intention using a quantitative method. The survey distribution and data collection focus on the three states’ residents. The findings are believed to be able to provide new insight and knowledge, especially to the healthcare providers and government to increase the vaccination rates in these states and prevent the severity of COVID-19 comeback.